Identity Crisis: Main Character’s Low Self-esteem in Kiko Draws a Feeling by Bob Raczka - Anisya Aulia (Morphosis: Journal of Literature, 2024)
This study, titled "Identity Crisis: Main Character’s Low Self-Esteem in Niko Draws a Feeling by Bob Raczka" (2017), examines the theme of identity crisis in the picture book and delves into the portrayal of this crisis and the protagonist’s coping mechanisms. The picture book follows the journey of a boy named Niko, who finds solace in drawing his surroundings: the jingle of the ice cream truck, the warmth of the sun on his face, and the diligent work of Mother Robin. Through his drawings, Niko expresses his emotions, sharing them with friends, family, and his teacher, only to encounter confusion in response. This rejection saddens him until he meets Iris, a new neighbor, who appreciates his artwork, bringing joy to Niko and fostering a newfound friendship. Employing a qualitative approach, this study utilizes Erikson’s psychosocial theory (1963) to explore the impact of low self-esteem on the protagonist’s identity crisis. Findings reveal that a deficiency in love, belonging, and appreciation can precipitate an identity crisis, resulting in internal turmoil and prompting self-transformation in the main character. Niko’s journey illustrates that through supportive relationships—be it with friends, teachers, or parents—he gains validation and a sense of unity, aiding him in navigating his identity crisis. Thus, the study underscores the significance of interpersonal connections in aiding protagonists in overcoming identity struggles. Keywords: identity crisis, isolated, picture book, psychosocial developed.